Three-dimensional biased proportional navigation guidance based on spatial rotation of predicted final velocity - Cho, Namhoon; Lee, Seokwon; Shin, Hyo-Sang; Kim, Tae-Hun (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This study presents the design of three-dimensional biased proportional navigation guidance laws for arrival at a stationary target along a desired direction based on spatial rotation of predicted final velocity vector. The focus is on full constructive derivation using vector-form expressions without introducing local representation of rotation such as Euler angles or quaternions. The proposed approach synthesises the bias command in the form of an angular velocity vector through realisation of the predictive control design philosophy, the direction which has been unexplored in a three-dimensional setting. The proposed approach avoids heuristic choices and approximations in the design process and hence overcomes the limitation of earlier studies. The vector-form design approach provides theoretical and practical advantages including rigour in derivation, clear geometric understandings about the problem provided by identification of the most effective direction for rotation of final velocity, independence from selection of a fixed coordinate system, avoidance of singularities in local representations, more direct trajectory shaping, and simple implementation.
Keywords: Three-Dimensional; Biased Proportional Navigation Guidance; Predictive Correction; Final Velocity Direction; Vector Rotation